Are Congenital Urinary Tract Abnormalities Linked to Maternal Methylenetetrahydrofolate Reductase Polymorphisms in Fetuses of Intentionally Terminated Pregnancies with Oligo- or Anhydramnios ?. (4th May 2018) - Beksac, M. Sinan; Beksac, Alp Tuna; Buyukeren, Melek; Tanacan, Atakan; Bektas, Hatice; Gucer, Safak
ABSTRACT: Objective: We aimed to evaluate fetuses of terminated pregnancies with oligo-or anhydramnios (OAH) to further investigate the association between maternal methylenetetrahydrofolate reductase (MTHFR) polymorphisms and fetal urinary tract malformations. Materials and Methods: This retrospective study included 16 pregnancies with OAH (with normal fetal karyotype) that were intentionally terminated before 22nd gestational week. Fetal autopsy was performed in all cases. We evaluated cases for presence of DNA methylation pathway-related gene polymorphisms. Results: We demonstrated that renal abnormalities and disorders exist in 75% of the cases. Pulmonary system anomalies and single umbilical artery were the most frequently observed associated abnormalities. Polymorphisms with known reduced MTHFR activity were found in 81.8% (9/11) of the cases.Association between urinary system abnormalities and polymorphisms with known reduced MTHFR activity was observed in 88.8% (8/9) of the cases. Conclusion: Physicians should keep in mind that polymorphisms with known reduced MTHFR activity may be associated with urinary tract abnormalities and OAH.